Spatial Reading of Jhumpa Lahiri’s Whereabouts - Talukdar, Susmita (AMERICANA E-journal of American Studies in Hungary, 2024)
Jhumpa Lahiri’s Whereabouts (2021) projects place that evokes both the senses of connection and loss for its unnamed narrator who, in her search of finding out her space in the world, fluctuates between what is immediate and distant. Her engagements with the surroundings and people at, in, and on various spaces/locations, and in different seasons seem to have become her own strategy of existence as she tries to negotiate with her loneliness in an unnamed city. My study problematises the narrative space of the novel. Should the narrative locations projected in the novel be considered as just physical settings in which the author is unfolding the plot, or do these, with the protagonist’s movement through them, expose the most crucial fundamental question of existence? The place becomes the most complex entity at which the author situates her character, as at various contexts those places take different significant meanings adding to the shifting meanings of contemporary life and purpose in the present age of global movement. The space in the contemporary global world of movement is slippery and both enticing and restrictive for human beings, causing dilemmas that result in man’s disappointment and loneliness. The paper explores how Lahiri’s text through its narrative space, produces socio-cultural and political place, and that further focuses on the psychic space delineating life enriched with varieties. My study attempts to overcome the rigid disciplinary boundary of English Literature without the theoretical constraints of several other academic disciplines, which would both make us critical of contemporary life yet sustain us with its varied resources.